FACTORS INFLUENCE VISITOR’S EXPERIENCE IN A SMALL-SCALE SPORTS EVENT - Anisah Abdul Wafi; Lim Khong Chiu; Kalsom Kayat, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
In order to provide the memorable experience and maintain the sustainability, event organizers should have knowledge and understanding regarding factors that influence the decision to attend an event. Limited understanding of these factors will influence the visitors’ decision to attend an event. In this respect, the purpose of this study is to identify factors (event image and satisfaction) which influence visitors’ decision to attend an event in the context of small-scale sport event. A total of 468 questionnaires was collected from visitors at the Pesta Sukan Sungai and Pesta Angin Timur, which held in the northern state in Malaysia. This study finds that, attraction and experience (event image) has the significant influence on the visitors’ decision to attend this small-scale sport event. Meanwhile, excitement and games attraction becomes the highest factor in visitors’ satisfaction. Thus, the managerial implications for marketing purposes are suggested and could be used as a reference for event marketers and organizers.